2010
DOI: 10.1116/1.3308623
|View full text |Cite
|
Sign up to set email alerts
|

Influence of C4F8/Ar-based etching and H2-based remote plasma ashing processes on ultralow k materials modifications

Abstract: Articles you may be interested inMechanistic study of ultralow k -compatible carbon dioxide in situ photoresist ashing processes. I. Process performance and influence on ULK material modification J. Vac. Sci. Technol. B 28, 952 (2010); 10.1116/1.3482343 Numerical simulation of dual frequency etching reactors: Influence of the external process parameters on the plasma characteristics J. Appl. Phys. 98, 023308 (2005); 10.1063/1.1989439 Study of C 4 F 8 / CO and C 4 F 8 / Ar/CO plasmas for highly selective etchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…1, the ash rate corresponding to the pure-N 2 plasma is zero, suggesting that N atoms alone cannot etch the photoresist in a remote-plasma environment. This is because the N radical density was found to increase continuously with increasing N 2 addition, 18,19 and this behavior is inconsistent with the trend for the photoresist ash rate as a function of N 2 concentration [ Fig. Further addition of N 2 , however, causes [H] to decrease.…”
Section: Reaction Mechanismsmentioning
confidence: 90%
See 1 more Smart Citation
“…1, the ash rate corresponding to the pure-N 2 plasma is zero, suggesting that N atoms alone cannot etch the photoresist in a remote-plasma environment. This is because the N radical density was found to increase continuously with increasing N 2 addition, 18,19 and this behavior is inconsistent with the trend for the photoresist ash rate as a function of N 2 concentration [ Fig. Further addition of N 2 , however, causes [H] to decrease.…”
Section: Reaction Mechanismsmentioning
confidence: 90%
“…Nagai et al found that the total electron density in the plasma environment increased substantially when a small amount of N 2 was added to H 2 plasma. 19 Regardless of the exact mechanism, the addition of a small amount of N 2 results in the enhanced dissociation of H 2 and, ultimately, gives rise to an increase in [H], which in turn increases the photoresist ash rate. The high electron density in turn enhances the dissociation of the H 2 into H atoms.…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…One is using different plasma gas chemistries to limit the low-j dielectric damage due to photoresist ashing by remote H 2 plasmas 12,13 or different combinations of Ar-and N 2 -containing plasmas. To mitigate these problems, several approaches have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Many groups have investigated the mechanisms of porous organosilicate modification during the exposure to fluorocarbon-based, 7,[10][11][12][13][14]16,18,21 oxygenbased, [7][8][9]11,15,17 and hydrogen-based [7][8][9]11,14,15,17 plasmas. 1-6 Porous organosilicate materials (SiCOH) are currently used in the most advanced integrated circuits.…”
Section: Introductionmentioning
confidence: 99%